Determination of trials needed for measurement consistency of standing long jump in female collegiate volleyball athletes: a brief report - Sue, R. A.; Harris, C.; Berning, J.; Sevene, T.; Adams, K. J.; DeBeliso, M. (International Journal of Sports Science, 2017)
Lower body power is an important physical attribute of competitive volleyball athletes. In order to assess such an attribute, it is important that the test reliability be established using a sport specific physical test and a participant pool consisting of competitive athletes. Furthermore, identification of the appropriate number of trials to use during assessment insures accuracy of scores and time efficiency for coaches. PURPOSE: The aim of this investigation was to establish the minimum number of trials needed for reliability of the standing long jump (SLJ) in female collegiate volleyball players. METHODS: Nine female athletes (age: 18.3±0.5yrs, height: 179.2±5.3cm, mass: 68.8±7.9kg) completed five trials of a SLJ. Jumps were performed at 2, 6, 10, 14 and 18 minutes following a dynamic warm-up. In an attempt to simulate the active nature of sport, the athletes alternated between walking and jogging the length of a basketball court between successive trials. For the SLJ, subjects performed a standard countermovement SLJ and distance in centimeters was measured from the starting line to the rear-most heel upon landing. Pearson (PCC) and Intraclass (ICC) Correlation Coefficients were calculated between successive trials. RESULTS: Means for the for the successive trials were as follows: Trial 1: 191.4±10.1cm; Trial 2: 196.1±10.2cm; Trial 3: 199.9±10.3; Trial 4: 199.6±11.8cm; Trial 5: 200.7±9.6cm. Mean difference between successive trials (i.e. Trials 2 to 1, 3 to 2, 4 to 3 and 5 to 4) were; 4.8±6.9, 3.8±5.5, -0.3±5.6 and 1.1±5.4 (cms). PCC and ICC for successive trials were: 0.77 and 0.82; 0.86 and 0.89; 0.88 and 0.91; 0.89 and 0.91. CONCLUSIONS: Given the parameters of this study, the SLJ is a reliable field test of horizontal muscular power output and adequate assessment of SLJ performance is achieved using three trials.